Development of Woodball Gate Using Acrylonitrile Butadiene Styrene Plastic Waste as a Conservation Effort in the Sports Environment - Indah Sari Dewi; Sulaiman; Agung Wahyudi (Journal of Physical Education and Sports, 2026)
This research was motivated by several problems, including the difficulty of installing woodball gates during the dry season, the iron at the bottom of the gate often coming loose when in use, the gate breaking when forced into place using a hard object, the gate easily becoming porous due to being frequently submerged in water during the rainy season, the iron at the bottom of the gate often shifting position due to loose soil, and the gate often being eaten by termites. The objective of this study is to develop a Gate Woodball using Acrylonitrile Butadiene Styrene (ABS) plastic waste material for woodball athlete training. The research design used was research and development (R&D). The sample consisted of 70 senior and junior athletes, as well as three senior and junior coaches in the sport of woodball. The development procedure used the Brog and Gall development model. The research instruments consisted of expert validation (woodball, plastic, construction), athlete response instruments, and coach response instruments. The results of the study indicate that the use of Gate Woodball made from Acrylonitrile Butadiene Styrene (ABS) plastic waste can serve as a new breakthrough and is well-received by the general public, including athletes and coaches. Gate Woodball made from ABS plastic waste is considered effective as one of the methods for processing plastic waste found in our surroundings and can accelerate the waste processing process. The analysis results indicate the advantages and disadvantages between wooden gates and gates made from Acrylonitrile Butadiene Styrene plastic waste. The gate made from Acrylonitrile Butadiene Styrene plastic waste has been proven effective for training senior and junior athletes in the sport of woodball to improve their finishing skills. The gate received a “Very Good” rating from experts and positive feedback from athletes and coaches. It is hoped that the results of this study will contribute to improving the finishing stroke skills of woodball athletes, inspire the general public to develop woodball gates using other materials, and serve as a reference for researchers and students in designing better woodball gates in the future.